A survey and analysis of the place-names of Staffordshire - Horovitz, David (2003)
This main body of this work consists of a gazetteer of all of the main, and many of the minor, place-names of Staffordshire (meaning any places which are or were at any time known to have been in what was, or became, Staffordshire), with early spellings, and observations on the likely or possible derivation of those names, often in a rather more discursive form than standard works on place-names, particularly where uncertainty exists as to the derivation. Early place-name spellings have been collected from many sources, primarily the volumes of the Staffordshire Historical Collections, but also the volumes of archive indexes at Staffordshire Record Office, supplemented by Staffordshire place-names extracted from other sources, such as the Transactions of the Shropshire Archaeological Society and the printed Cartularies of Haughmond and Lilleshall Abbeys, both in Shropshire, and from the editorial notes produced during research by the Victoria County History of Staffordshire team. Those slips often contain early place-name spellings. The Staffordshire Encyclopaedia, a monumental compilation of material on the history and folk-lore of Staffordshire published in 2000, has provided a valuable key to material relating indirectly to place-name research, such as topographical and archaeological features. Other material has been extracted from early work on the place-names of Staffordshire and adjoining counties by W. H. Duignan and from other volumes on place-name research and the journals of The English Place-Name Society and The Society for Name Studies in Britain and Ireland.